Secession and Federalism in Austrian School’s Perspective - Silva, Daniela Sofia Gomes da; Alves, André Azevedo (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2013)
In order to make known the concept of secession from the perspective of the Austrian School, this work considers the contributions of several authors that help us to better understand how this option relates with the idea of inter-territorial competition. In this sense, secession is presented together with the concept of polycentricity, which in turn, is related with the theoretical discussion about federalism. Bringing together the central ideas of the Austrian School with those Political Theory concepts, several arguments are presented in support of the decentralisation as a means of limitating power.